Undiagnosed cardiovascular risk factors including elevated lipoprotein(a) in patients with ischaemic heart disease - Chua, Fionn; Lam, Audrey; Mak, Ying Hui; Lee, Zhong Hui; Dacay, Lily Mae; Yew, Jie Lin; Puar, Troy; Khoo, Joan; Chow, Weien; Tan, Vern Hsen; Tong, Khim Leng; Liew, Boon Wah; et al. (Frontiers in Epidemiology, 2023)
Objectives: This study aims to investigate the prevalence of undiagnosed cardiovascular risk factors in patients with ischaemic heart disease (IHD).We assessed the prevalence of previously undiagnosed cardiovascular risk factors, including elevated lipoprotein(a) [Lp(a)], among consenting patients with IHD who were admitted to hospital. Clinical information, including dietary history, from patients with newly diagnosed IHD and known IHD were compared.Results: Of the 555 patients, 82.3% were males and 48.5% of Chinese ethnicity. Overall, 13.3% were newly diagnosed with hypertension, 14.8% with hypercholesterolemia, and 5% with type 2 diabetes (T2DM). Patients with newly diagnosed IHD, compared to those with known IHD, had a higher prevalence of new diagnoses of hypercholesterolemia (29.1% vs 2.0%, p<0.001), hypertension (24.5% vs 3.4%, p<0.001) and T2DM (7.3% vs 3.1%, p=0.023). Active smoking was prevalent in 28.3% of patients, and higher in newly diagnosed IHD (34.1% vs 23.2%, p =0.005). Elevated Lp(a) of ≥120 nmol/L was detected in 15.6% of all patients, none of whom were previously diagnosed. Dietary habits of >50% of patients in both groups did not meet national recommendations for fruits, vegetables, wholegrain and oily fish intake. However, patients with known IHD had a more regular omega-3 supplement intake (23.4% vs 10.3%, p=0.024).Increased detection efforts is necessary to diagnose chronic metabolic diseases (hypertension, hypercholesterolemia, T2DM) especially among patients at high risk for IHD. Cardiovascular risk factors, in particular elevated Lp(a), smoking, and suboptimal dietary intake in patients with IHD deserve further attention.